The role of the registered nurse in the marketing of primary healthcare services, as part of health promotion - M Rail; SM Meyer (AOSIS, 2006)
Existing literature on the marketing of primary healthcare services was reviewed to determine the role of registered nurses in this regard. The systematic review included "- five searches and ensured wide coverage of the results of available primary research studies on the topic. The results were summarised and the role of registered nurses in the marketing of primary healthcare services was identified. Primary research sources on the topic included textbooks on marketing by experts in the field and relevant journal articles by authorities on healthcare marketing. The data were analysed and four main categories identified. To ensure the trustworthiness of the research, Lincoln and Guba's (1981:215-216) criteria, as explained by Krefting (1991:217), were applied. Because the population consisted of only literature, ethical considerations concerning human subjects were irrelevant. Results indicated that the basic commercial marketing principles (the so-called 4Ps - product, price, place, and promotion) could be adapted for the health sector. The conclusion was that registered nurses could contribute to the marketing of primary healthcare services by communicating with the community (promotion) and by ensuring effective service (product) delivery at the right price and place. Registered nurses could influence the community's perceptions of health care and facilitate behaviour changes, thereby promote health. The implementation of the findings and recommendations of this research could create a new awareness among registered nurses of their role in the marketing of primary healthcare services in South Africa and improve their skills in this regard.